Halâl-Harâm Risywah dalam Tinjauan Hukum Islam: Kajian Heuristik tentang Ayat-Ayat Risywah dalam Al-Qur’an - Udin Saprudin (ALSYS, 2025)
This study departs from the prevalence of risywah (bribery), which is often normalized through euphemistic terms, while research that specifically examines the halal–haram status of risywah based on Qur’anic verses remains limited. The study aims to elucidate the nature of risywah, the boundaries of its permissibility and prohibition, and its impact on individuals, society, and the state from the perspective of Islamic law. A qualitative method with a library research design was employed, using a heuristic examination of verses on risywah in the Al-Qur’an. Data were collected through documentation of the Al-Qur’an, classical and modern exegetical works, and fiqh literature, and were subsequently analyzed using a linguistic approach, historical analysis of asbāb an-nuzūl, and thematic coherence analysis (munāsabah). The findings show that risywah is fundamentally and unequivocally prohibited (haram) because it undermines justice, deprives individuals of their rights, and generates socio-political corruption, whereas claims of its “permissibility” generally arise from the misuse of terms such as gifts, tokens of appreciation, or administrative fees. Accordingly, the prohibition of risywah constitutes a basic principle in Islamic law that functions both preventively and correctively against various forms of corruption. The implications of this study underscore the importance of integrating Qur’anic values into the formulation of anti-corruption regulations and strengthening the ethical standards of law enforcement officers in Muslim-majority countries.